Spreading and mutability of Selenomonas ruminantium plasmids - Ivan, J; Sprincová, A; Javorský, P; Pristas, P (Folia microbiologica, 2006)
Two small plasmids from Selenomonas ruminantium strain 19D were cloned in Escherichia coli and completely characterized. Sequence comparison indicated that the plasmids are similar to those reported in genetically vaguely related S. ruminantium strain S20. Small 1.4-kb plasmids pSRD191 and pONE430 are only distantly related (approximately 30 % for deduced Rep protein amino acid sequence) but possess a short highly conserved region outside rep gene. Larger plasmids pSRD192 and pONE429 possess large identical DNA regions in an otherwise dissimilar background. Recombination is proposed as an important mechanism of evolution and spreading of S. ruminantium plasmids.
Keywords: DNA, Circular; plazmidy; rekombinace genetická; Molecular Sequence Data; molekulární sekvence - údaje; Plasmids; Sequence Homology, Nucleic Acid; sekvenční homologie nukleových kyselin; Animals; Sequence Alignment; Escherichia coli; kruhová DNA; Selenomonas; Ruminants; přežvýkavci; sekvenční seřazení; zvířata; Recombination, Genetic